2020
DOI: 10.1111/ijlh.13273
|View full text |Cite
|
Sign up to set email alerts
|

Manifestations of blood coagulation and its relation to clinical outcomes in severe COVID‐19 patients: Retrospective analysis

Abstract: Introduction: Characteristics of blood coagulation and its relation to clinical outcomes in COVID-19 patients are still rarely reported. We aimed to investigate the blood coagulation function and its influences on clinical outcomes of patients with syndrome coronavirus 2 (SARS-CoV-2) infection. Methods: A total of 71 severe patients with confirmed SARS-CoV-2 infection who were treated in Wuhan First Hospital from February 12 to March 20, 2020, were enrolled. The blood coagulation data in these patients and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…Noteworthy, patients with severe SARS-CoV-2 infection often possess coagulation dysfunction at admission [34]. A recent study by Zhang et al demonstrated that INR was a prognostic factor for clinical outcomes in patients with severe COVID-19 [34]. In the present study, we observed that there was also significant in the INR between survival and non-survival group in univariate analysis.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Noteworthy, patients with severe SARS-CoV-2 infection often possess coagulation dysfunction at admission [34]. A recent study by Zhang et al demonstrated that INR was a prognostic factor for clinical outcomes in patients with severe COVID-19 [34]. In the present study, we observed that there was also significant in the INR between survival and non-survival group in univariate analysis.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, it is not difficult to understand that platelets and D-dimers are independent risk factors that affect the outcome of patients. Noteworthy, patients with severe SARS-CoV-2 infection often possess coagulation dysfunction at admission [34]. A recent study by Zhang et al demonstrated that INR was a prognostic factor for clinical outcomes in patients with severe COVID-19 [34].…”
Section: Discussionmentioning
confidence: 99%
“… 52 In this study, D-dimer, fibrin degradation products, prothrombin time, and partial thromboplastin time all were significantly increased in nonsurviving patients relative to those surviving COVID-19. 53 Additional studies demonstrate a prothrombotic state in certain patients, with 7 of 12 patients having deep venous thromboses on autopsy. 54 The mechanisms of this COVID-related coagulopathy are not yet well described in the literature; however, these undefined entities pose certain risk for reconstructive efforts in patients with head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The most common was an alteration in fibrinogen and D-dimer levels, prolonged prothrombin time (PT), and prolonged activated partial thromboplastin time (APTT) [ 50 ]. The amount of D-dimer was higher in patients with severe than mild infection in a related study performed at Wuhan First Hospital, China [ 51 ]. Similarly, mean levels of fibrinogen, D-dimer, and von Willebrand factor (VWF) were shown to be significantly increased in a study conducted in Milan, Italy, on COVID-19 patients in the intensive care unit (ICU).…”
Section: Hypercoagulopathy Associated With Sars-cov-2 Infectionmentioning
confidence: 99%